Normal Aging Induces Changes in the Brain and Neurodegeneration Progress: Review of the Structural, Biochemical, Metabolic, Cellular, and Molecular Changes - Lee, Jiseon; Kim, Hee-Jin (Frontiers in Aging Neuroscience, 2022)
Aging is accompanied by many changes in brain and contributes to progressive cognitive decline. In contrast to pathological changes in brain, normal aging brain changes have relatively mild but important changes in structural, biochemical and molecular level. Representatively, aging associated brain changes include atrophy of tissues, alteration in neurotransmitters and damage accumulation in cellular environment. These effects have causative link with age associated cognitive decline. Although several evidences were found in normal aging changes of brain, it is not clearly integrated. Figuring out aging related changes in brain is important as aging is the process that everyone goes through, and comprehensive understanding may help to progress further studies. This review clarifies normal aging brain changes in an asymptotic manner, from gross level to the microscopic level and to the molecular level, and discusses potential approaches to integrate changes gradually, and seeks the changes with cognitive decline.